An Examination of Academic Procrastination Levels among Undergraduate Kuwait University Students and their Effect on some Demographic Variables. - BOUHMAMA, Djilali (Journal of Human Sciences, 2018)
The present research is aimed to investigate the academic procrastination levels among undergraduate Kuwait University students and to explore the effect of some demographic variables namely gender, and academic achievement. The sample consisted of 300 students (150 males and 150 females) from the college of education, Kuwait University. They ranged in age from 18 to 27 (M = 19.51, SD= 1.77) An academic procrastination scale was developed by the author and used for the collection of data. The results showed that the overall mean of academic procrastination of the whole sample reached 3.68 which means that the participants in the study exhibited high procrastination tendency.The results also indicated significant gender differences among males and females on academic procrastination.Male students procrastinate more than female students.The results further showed that high level procrastinators tend to achieve low academic achievement than lower level procrastinators, and therefore the academic procrastination is related to lower levels of academic achievement.The findings were discussed in the light of the relevant literature and some suggestions for further studies were formulated.